Association of cardiac autonomic modulation with physical and clinical features of young people with type 1 diabetes - Silva, Anne K. F. [UNESP]; Christofaro, Diego G. D. [UNESP]; Vanderlei, Franciele M. [UNESP]; Barbosa, Marianne P. C. R. [UNESP]; Garner, David M.; Vanderlei, Luiz C. M. [UNESP] (Cambridge Univ Press, 2017)
Objective: The objective of this study was to verify possible associations between heart rate variability indices and physical activity, body composition, and metabolic and cardiovascular parameters in individuals with type 1 diabetes. Method: A total of 39 young patients with type 1 diabetes were included. Body composition, physical activity, cardiovascular parameters, and metabolic parameters were assessed. For the heart rate variability analysis, heart rate was recorded beat-by-beat using a Polar S810i heart rate monitor for 30 minutes, with the volunteers in the supine position; subsequently, the following indices were considered: standard deviation of all normal RR intervals; root-mean square of differences between adjacent normal RR intervals in a time interval; percentage of adjacent RR intervals with a difference of duration >50 ms; high frequency component in milliseconds squared; high frequency component in normalised units; standard deviation of the instantaneous variability beat-to-beat; and standard deviation of the long-term variability. The association between the heart rate variability indices and independent variables was verified through linear regression in unadjusted and adjusted models (considering gender and age). The statistical significance was set at 5% and the confidence interval at 95%. Results: High values of at-rest heart rate were associated with reduced parasympathetic activity and global heart rate variability, and higher values of waist-to-hip ratio were related to lower parasympathetic activity, independent of age or gender. Conclusion: For young patients with type 1 diabetes, increases in at-rest heart rate values are associated with reduced parasympathetic activity and global heart rate variability, whereas higher waist-to-hip ratio values are related to lower parasympathetic activity, both independent of age and gender.
Keywords: Diabetes mellitus type 1 autonomic nervous system; risk factors; heart rate; young adult